Structural lesions detected by magnetic resonance imaging in the spine of patients with spondyloarthritis - Definitions, assessment system, and reference image set - Mikkel Østergaard (2018)
Objective. There is no reliable and sensitive magnetic resonance imaging (MRI) assessment system for structural lesions in patients with spondyloarthritis (SpA). We sought to develop and illustrate a detailed anatomy-based set of MRI definitions and an assessment system for structural lesions in the spine of patients with SpA. Methods. MRI definitions of different structural ("chronic") lesions at various anatomical locations in the spine, and an accompanying assessment system, were agreed by consensus within the Canada-Denmark MRI working group. Subsequently, a reference image set of representative examples of the individual pathologies, as well as borderline cases and important artefacts, were collected. Results. The defined lesions were (a) Bone erosions, subdivided into corner and non-corner vertebral body erosions and facet joint erosions; (b) Focal fat infiltration at vertebral corners; (c) Bone spurs, subdivided into corner and non-corner vertebral body spurs; and (d) Ankylosis, subdivided into corner and non-corner vertebral body ankylosis and facet joint ankylosis. All definitions were based on their appearance on sagittal T1-weighted MR images. Vertebral body structural lesions are assessed at each vertebral endplate at all 23 spinal levels from C2/3 to L5/S1, whereas facet joint lesions are to be assessed by segmental level (cervical, thoracic, and lumbar). Conclusion. An anatomy-based set of definitions and an assessment system for structural lesions in the spine of patients with SpA were developed and illustrated. The system is designed to study the spatial pattern of the lesions and their relation to spine inflammation and clinical and radiographic outcomes. Copyright © 2009. All rights reserved.